Análisis de la política social en el periodo de Rafael Correa periodo 20072017 - Castillo Aguilar, Jose Antonio (2018)
Abstract:In the present work, the social policy in Ecuador during the presidential period of Rafael Correa is analyzed; in addition to the national programs that contributed to the improvement of the social sectors based on the National Development Plans (PND) 2007-2010 "Planning for the Citizen Revolution" and the National Plan for Good Living (PNBV) 2009-2013 "Building a Plurinational and Intercultural State ". Among these PND, there are 29 programs that contributed to the improvement of the social sectors: education, social welfare, employment and health, which are evaluated through the method of review and evaluation of objectives. One of the results obtained that was achieved through the objective evaluation method is that the Human Development Bond (BDH) program is very efficient for the reduction of poverty.